Perioperative SARS-CoV-2 Infection in Patients Undergoing Elective Surgery in Gynecology Clinic: Tertiary Center Experience - Gulnihal Reyhan Toptas; Eylem Unlubilgin; Tugba Kinay; Ali Riza Dogan; Mehmet Akif Akgul; Sitare Aslanova; Emel Ebru Ercan; Vakkas Korkmaz; Sezin Erturk Aksakal; Yaprak Ustun (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: The objective of this study was to determine the incidence of perioperative “severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2)” infection among women, operated during Coronavirus disease-2019 (COVID-19) era.